Xuebijing Injection Alleviates Sepsis-Induced Acute Lung Injury by Inhibition of Cell Apoptosis and Inflammation Through the Hippo Pathway - Ling B; Ji J; Huang Q; Xu Y; Hu Y; Pan S; Liu S; Hua T; Tang L; Yang M (Journal of Inflammation Research, 2025)
Bingrui Ling,1,2,* Jinlu Ji,3,4,* Qihui Huang,1,2 Yang Xu,1,2 Yan Hu,1,2 Sinong Pan,1,2 Siying Liu,1,2 Tianfeng Hua,1,2 Lunxian Tang,3,4 Min Yang1,2 1The Second Department of Intensive Care Unit, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230601, People’s Republic of China; 2The Laboratory of Cardiopulmonary Resuscitation and Critical Care Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230601, People’s Republic of China; 3Department of Internal Emergency Medicine, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China; 4School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lunxian Tang, Department of Internal Emergency Medicine, Shanghai East Hospital, School of Medicine, Tongji University, 551 South Pudong Road, Shanghai, 200092, People’s Republic of China, Tel +86 18916290981, Email 456tlx@163.com Min Yang, The Second Department of Critical Care Medicine, The Second Affiliated Hospital of Anhui Medical University, 678 Furong Road, Hefei, Anhui, 230601, People’s Republic of China, Tel +86 13721040363, Email yangmin@ahmu.edu.cnBackground: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is a critical complication of sepsis, strongly associated with poor prognosis. Xuebijing (XBJ) injection, a standardized multi-herbal formulation containing five active components (safflower, red peony, Chuanxiong, Salvia miltiorrhiza, and Angelica sinensis), has demonstrated clinical efficacy in sepsis management through its multimodal pharmacological actions. While XBJ is increasingly used as an adjunctive therapy for sepsis-induced ALI/ARDS, its specific protective mechanisms remain incompletely understood. The purpose of this study was to evaluate the improvement effect of XBJ injection on ALI in sepsis and its undefined molecular mechanism.Methods: Sepsis-induced ALI (SALI) murine animal model was established in rats by cecum ligation and puncture (CLP), and these rats were treated with or without XBJ injection. Lung injury across different groups was assessed by HE staining, W/D ratio, and BALF analysis. ZO-1 and CD31 immunofluorescence were used to evaluate endothelial damage. To illustrate the mechanism of the protective effect of XBJ on SALI, human umbilical vein endothelial cells (HUVECs) stimulated with lipopolysaccharide (LPS) were used to establish an in vitro endothelial inflammation model. Inflammatory cytokines and apoptotic proteins were measured in LPS-stimulated HUVECs to evaluate endothelial inflammation. Lung tissue transcriptomic analysis was performed to explore downstream pathway, and key Hippo pathway related proteins were assessed in both rat lung tissue and HUVECs.Results: In SALI animal models, treatment with XBJ significantly alleviated lung injury. Meanwhile, a substantial amelioration of endothelial damage was observed. In vitro, XBJ substantially mitigated apoptosis and inflammatory response of LPS stimulated HUVECs. Meanwhile, transcriptomic analysis revealed that XBJ significantly upregulates the gene expression of the Hippo-related signaling pathway, and we further validated these findings in both rat lung tissues and HUVECs.Conclusion: Our study establishes the preventive role of XBJ injection in SALI by alleviating apoptosis and inflammatory response partially through regulating the Hippo pathway. Keywords: sepsis, acute lung injury, Xuebijing, inflammatory response, cell apoptosis, Hippo signaling pathway